The shared fish stocks conservation: revisiting the unconnected enforcement - Rachma Indriyani; Asmar Binti Abdul Rahim; Ruzita Binti Azmi (Legality : Jurnal Ilmiah Hukum, 2021)
“There is plenty of other fish in the sea," goes the old cliché as many stocks have been overfished by industrial fisheries, that the over-activity made some fish species in danger. The scope of this paper covers the enforcement issue of Southern Bluefin Tuna (SBT) as endangered fish species. Taking Indonesia, New Zealand, and Australia as member States who catch SBT, this paper is a conceptual study using content analysis aiming to review how these three-member States officially treat SBT stocks. Based on the discussion, it found that since the shared characteristic of SBT, in areas beyond national jurisdiction it might create regulatory gaps. While international provisions have been entered into force in respect of endangered fish stocks in high seas areas, however, a lacuna remained in which the law cannot reach the national fishing area. This situation may lead to a discrepancy framework at the national level. Therefore, this paper argues that connectivity is crucial to link enforcement among relevant States with the real interest. In this context, the enforcement must consider the movement path of SBT from a coastal State (the spawning ground), the flag State (the fishing vessel), and the Port State (the place to land SBT).